Pemanfaatan bioinformatika dalam bidang pertanian dan kesehatan (The utilization of bioinformatics in the field of agriculture and health) - Arli Aditya PARIKESIT; Dito ANUROGO; Riza A PUTRANTO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2017)
Bioinformatics can be used to manage the data storage resulted from in silico molecular biology experiments. Off-network (offline) applications require large computing resources, in which researchers in the bioinformatics field of agriculture and health sectors do not necessarily possess. This review paper addressed examples of affordable and applicable in silico analytical cases in both mentioned sectors. Genome sequence analysis and in silico drug design using (1) a computational method, pharmacokinetic parameter prediction, (2) Computer Aided Design and Drafting (CADD) technology, (3) potential protein action prediction, (4) OMICs application in stem cell biology, and (5) lncRNAs based database computing internet sites is one of examples. In agriculture, bioinformatics-based research has been used in (1) the development of molecular markers; (2) the design of primer for differential gene expression analysis; (3) the development of genetic maps; and (4) gene expression analysis. Further application of bioinformatics also targets the design of applicative products for pest control and the protection of plant varieties in the farm. Through this example, novice researchers in the bioinformatics field of agriculture and health sectors can conduct sophisticated research using standard computer tools, internet networks, and sufficient knowledge about bioinformatics. On the other hand, multidisciplinary collaboration between these scientists can be carried out through social networking. The synergy can be directed to improve computing capabilities and data analysis via procurement of computing resources and use of public information clusters. [Key words: genome sequences, in silico drug design, online, bioinformatics, health, agriculture.] AbstrakBioinformatika dapat digunakan dalam manajemen informasi di bidang penyimpanan data in silico dari eksperimen biologi molekuler. Aplikasi luar jaringan (luring) memerlukan sumber daya komputasi yang besar, yang belum tentu dimiliki oleh para peneliti dalam bidang bioinformatika kesehatan dan pertanian. Kajian ilmiah ini membahas contoh kasus analisis in silico yang terjangkau dan aplikatif dalam bidang kesehatan dan pertanian. Contoh kasus tersebut adalah analisis sekuen genom dan desain obat in silico, menggunakan pendekatan metode komputasional, prediksi parameter farmakokinetik, teknologi Computer Aided Design and Drafting (CADD), prediksi potensial aksi protein, aplikasi OMICs pada biologi sel punca, hingga komputasi basis data lncRNAs berbasis situs internet. Pada bidang pertanian, penelitian berbasis bioinformatika telah digunakan dalam (1) pengembangan penanda molekuler; (2) desain primer untuk analisis ekspresi gen diferensial; (3) pengembangan peta genetik; dan (4) analisis ekspresi gen. Pemanfaatan bio-informatika dalam ilmu terapan dibidang pertanian juga menyasar desain produk aplikatif untuk pengendalian hama dan perlindungan varietas tanaman. Melalui contoh tersebut, peneliti pemula dibidang bioinformatika kesehatan dan pertanian dapat melakukan penelitian canggih hanya dengan alat komputer standar, jaringan internet, dan pengetahuan mencukupi tentang bioinformatika. Disisi lain, sinergi dan kolaborasi antar peneliti multi-displiner dapat dilakukan melalui penggunaan jejaring sosial. Sinergi tersebut dapat diarahkan untuk meningkatkan kemampuan komputasi dan analisis data melalui pengadaan sumber daya komputasi dan penggunaan klaster informatika publik.[Kata kunci: sekuen genom, desain obat in silico, daring, bioinformatika, kesehatan, pertanian]